The Fair Dealing Exception Explained: A 20 Year Retrospective - Shannon, Meagan; Swartz, Mark (Journal of Copyright in Education & Librarianship, 2025)
This paper is intended for library practitioners and information professionals, presenting a deep dive into the Canadian case law that relates to fair dealing, a user’s right, with a particular focus on CCH and subsequent cases from 2004 to 2024. Readers will learn the importance of fair dealing, discovering how decisions from the courts can be used to help users of copyrighted works conduct fair dealing analyses by considering the six fair dealing factors prescribed by the Supreme Court of Canada in CCH. This “paper” does not follow a typical structure expected of a research paper, and is not meant to be read as a complete work. Rather, the summaries and excerpts provided below are to be used as references for those researching fair dealing or conducting fair dealing analyses. The genesis of the 2024 ABC Copyright Conference presentation, available in the ABC 2024 collection and copies of all cases referenced in both our presentation and this paper are available in an open reading list.